The ALMA frontier fields survey: IV. lensing-corrected 1.1 mm number counts in Abell 2744, MACS J0416.1−2403, and MACS J1149.5+2223 (Corrigendum) - Muñoz Arancibia, Alejandra; Carrasco, Mauricio (Astronomy and astrophysics, 2019)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 05.02.2020